Between the image and the word : theological engagements with imagination, language, and literature - Hart, Trevor (Farnham : Ashgate Publishing Ltd, 2013)
The central contention of Christian faith is that in the incarnation the eternal Word or Logos of God himself has taken flesh, so becoming for us the image of the invisible God. Our humanity itself is lived out in a constant toing and froing between materiality and immateriality.Approaching different aspects of two distinct movements between the image and the word, in the incarnation and in the dynamics of human existence itself, Trevor Hart presents a clearer understanding of each and explores the juxtapositions with the other.
Cover; Contents; Provenance of Chapters; Introduction; 1 Between the Image and the Word; 2 The Promise and the Sign; 3 The Economy of the Flesh; 4 The Grammar of Conversation; 5 Cosmos, Kenosis and Creativity; 6 Unauthorised Texts; 7 Unseemly Representations; 8 Unfinished Performances; 9 Unexpected Endings; 10 The Substance of Things Hoped For; Index
Includes index.
Description based on print version record.
Keywords: Incarnation; Imagination -- Religious aspects -- Christianity; Language and languages -- Religious aspects -- Christianity; Theology in literature